Synthesis of CdS and alloyed CdMnS nanocrystals using aqueous foams - Kumar, P. Senthil; Kasture, Manasi; Raghavan, U; Pasricha, R; Sastry, M (Journal of Nanoscience and Nanotechnology, 2005)
Certain surfactant-stabilized aqueous foams provide a potentially efficient and simple chemical route for the synthesis of various nanomaterials with controllable structure, size, and shape. In the present work, a one-step process for the synthesis of CdS and Cdl(1-x)Mn(x)S (0 < x < 10) nanocrystals has been described. Aqueous CdCl2 and the aerosol-OT solutions are homogeneously mixed together and thereafter, nitrogen is bubbled through this solution to produce stable aqueous foam. After drainage of the foam, the freestanding dry foam consisting of cadmium cations electrostatically complexed with the anionic aerosol-OT molecules at the liquid-gas interface is treated with H2S vapor. The foam turns yellowish-orange and collapses, in the process yielding CdS nanoclusters of variable morphology. This morphology variation is appropriately attributed to growth of the CdS as well as alloyed Cd1-xMnxS nanoparticles in different regions of the foam contributing to the varying topological structure. Optical absorption spectra of both CdS and Cd1-xMnxS nanoparticles clearly show a well-defined exciton absorption feature around 450 nm due to quantum confinement effects. The interesting band edge emission characteristics of these AOT-capped CdS and Cd1-xMnxS nanoparticles produced in the foam are discussed with respect to their size and shape. Particular interest in the present novel aqueous foam approach arises due to the fact that the cubic zincblende CdS and alloyed Cd1-xMnxS nanocrystals could easily be obtained even under ambient experimental conditions itself.
Keywords: absorption and fluorescence; aerosol-OT; alloyed CdMnS nanocrystals; aqueous foams; CdS nanoclusters; quantum confinement; zincblende